Origin of Roman worked stones from St. Saturno christian Basilica (south Sardinia, Italy) - Columbu, Stefano (2018)
The work aims to define the origin of the architectural stone elements worked by Romans and reused in the St. Saturno Basilica, between the late Antiquity and Romanesque periods. Thus, different rocks (marbles, various facies of limestones, volcanic rocks) used to construct the ancient building were sampled and ana- lysed. All the different kinds of stones were sampled from the Basilica, taking precise reference to the vari- ous construction phases and structural changes of the monument occurred in the centuries. The sedimentary and volcanic lithologies belong to the local outcrops of Cagliari Miocenic geological for- mation (e.g. limestone) and to other volcanic outcrops of south Sardinia, respectively. By means of a multi- method archaeometric study (mineralogical-petrographic observations on thin sections and 18O vs 13C stable isotope ratio analysis), the provenance of classical marbles used for manufacturing Roman architectural ele- ments (column shafts, bases, capitals, slabs, etc.) were defined, which are thought to come from extra- regional sources. The results show that the marbles come mainly from Apuan Alps (Italy) and subordinately from Greek quarrying areas.